Contagion and the subject in contemporary American speculative fiction - Donner, Mathieu (2017)
This thesis explores the relationship between the representation of contagion and those it affects offered by contemporary American speculative fiction and the ways in which this representative model has and continues to inform our understanding of real and actual pandemics. Over the past decade, the success of texts centred on such figures as the vampire, the werewolf and the zombie has triggered a return of contagion to the forefront of the American popular fictional imagination. Though this renewed fascination coincides with the emergence of new global biological threats, it also draws part of its power from a broader cultural anxiety regarding the structures of subjectivity, the relation between subject and State as well as the subject’s role within the collective deployed by our contemporary discourse of health. While critical studies on contagion have been predominantly concerned with real diseases and their narrativisation, this thesis focuses on five fictional representations—Robert Kirkman’s The Walking Dead, Richard Matheson’s I Am Legend and its adaptations, the American series Being Human, Octavia E. Butler’s Clay’s Ark and Charles Burns’s Black Hole—in order to explore the ways in which these texts engage with the modern medical discourse and the wider conceptualisation of subjectivity promoted by Western philosophy. By emptying the referential dimension of the diseases they mobilise, these texts provide a unique opportunity to analyse the underlying mechanisms of contagion as a cultural construction and to expose the set of assumptions (moral, political, social, etc.) upon which its production itself relies. Exposing the ways in which our cultural perception of contagion has been shaped by the limitations inherent to the traditional epistemic model dominating Western society, this thesis not only reveal the violence inherent in the structures of subjectivity surrounding the individual, it also highlights, by deconstructing the dominant model, new possible lines of flight for the contagious subject outside the normative structures of our current public health, medical, social and political discourses.